Optimizing Growth and Survival of Oreochromis niloticus Using Varying Levels of Kepok Banana (Musa balbisiana) Peel Powder in Feed - Helentina Mariance Manullang; Uswatul Hasan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to evaluate the effects of different dietary inclusion levels of kepok banana (Musa paradisiaca) peel powder on the growth performance, survival, and feed efficiency of GIFT tilapia (Oreochromis niloticus) fry. A completely randomized design was used, consisting of four treatments: A = 0%, B = 10%, C = 15%, and D = 20% banana peel powder, with four replicates per treatment. A total of 160 fingerlings measuring 3–5 cm were reared in 16 aerated buckets for 30 days. The observed parameters included survival rate, absolute weight gain, absolute length gain, feed conversion ratio (FCR), and water quality. The FCR was calculated for each bucket using the formula: FCR = total feed consumed / total weight gain. The results showed that Treatment B, with 10% banana peel powder inclusion, produced the highest survival rate (85 ± 5.77%), absolute weight gain (2.92 ± 0.13 g), and absolute length gain (2.40 ± 0.08 cm), as well as the lowest FCR (1.63 ± 0.29). This treatment significantly outperformed the other treatments based on ANOVA analysis (p < 0.05). Water quality remained within optimal ranges throughout the study, with temperature ranging from 28.12 to 28.19°C, pH from 7.19 to 7.36, and dissolved oxygen from 6.13 to 6.28 ml/L. These findings indicate that 10% dietary inclusion of banana peel powder can optimize growth performance and feed efficiency without compromising survival, thereby providing a locally available alternative feed ingredient for tilapia fry.